DNA Methylation Changes Are Associated With an Incremental Ascent to High Altitude - Childebayeva, Ainash; Harman, Taylor; Weinstein, Julien; Goodrich, Jaclyn M.; Dolinoy, Dana C.; Day, Trevor A.; Bigham, Abigail W.; Brutsaert, Tom D. (Frontiers in Genetics, 2019)
Genetic and non-genetic factors are involved in the individual ability to physiologically acclimatize to high-altitude hypoxia. Increased heart rate and ventilation are associated with response to high-altitude exposure. High-altitude acclimatization is known to have a genetic component. Yet, it is unclear if other factors, such as epigenetic gene regulation, are involved in acclimatization to high-altitude hypoxia in non-acclimatized individuals. We collected saliva samples from a group of healthy adults of European ancestry (n=21) in Kathmandu (1400 m; baseline) and three altitudes during a trek to the Everest Base Camp: Namche (3440 m; day three), Pheriche (4240 m; day seven), and Gorak Shep (5160 m; day 10). We used quantitative bisulfite pyrosequencing to determine changes in DNA methylation, a well-studied epigenetic marker, in LINE-1, EPAS1, EPO, PPARa, and RXRa. We found significantly lower DNA methylation between baseline (1400 m) and high altitudes in LINE-1, EPO (at 4240 m only), and RXRa. We found increased methylation in EPAS1 (at 4240m only) and PPARa. We also found positive associations between EPO methylation and systolic blood pressure and RXRa methylation and hemoglobin. Our results show that incremental exposure to hypoxia can affect the epigenome. Changes to the epigenome, in turn, could underlie the process of altitude acclimatization.